Ekowisata di Kawasan Vulkanik: Tinjauan Pustaka Sistematis tentang Dampak terhadap Komunitas, Keterlibatan Pemangku Kepentingan, dan Implikasi Pembangunan - Abdul Kadir Kamaluddin; Abdul Wahab Hasyim; Lily Ishak; Sulfi Abdul Haji (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
This study conducts a systematic literature review to explore the dynamics of ecotourism in volcanic regions, with a particular focus on its impact on communities and stakeholders. The review was carried out using the PRISMA protocol, focusing on literature published between January 2002 and May 2024 in the Scopus database. An initial pool of 40 articles was filtered through inclusion and exclusion criteria, resulting in 14 eligible studies for synthesis. The findings reveal diverse impacts of ecotourism in volcanic areas, including economic benefits, conservation challenges, sociocultural transformations, and stakeholder governance. Notably, most studies concentrated on the tourism sector, with limited coverage of other relevant industries. The review also identifies methodological and theoretical gaps, with few studies employing explicit theoretical frameworks. This study contributes to the academic discourse by mapping existing knowledge, identifying thematic clusters, and offering practical recommendations for policy and future research aimed at enhancing the sustainability and inclusivity of ecotourism in volcanic landscapes.